Manajemen Kesehatan Reproduksi Pada Remaja - Andry Sartika; Ferasinta Ferasinta; Panzilion Panzilion (JURNAL PENGABDIAN KESEHATAN, 2023)
ABSTRACT Adolescents with anemia, adolescents with unwanted pregnancies, adolescents with early marriages, and free sex. The root cause of the emergence of these problems is the lack of knowledge of adolescents about reproductive health. The high number of teenagers in Indonesia is also accompanied by the problems faced by them. Of the various teenage problems that have arisen, the issue of sexuality has received the most attention from various groups. Adolescents often lack basic information about reproductive health and access to reproductive health services that are affordable and guaranteed confidentiality. Concerns about guarantees of confidentiality or the ability to pay, and the fact or perceptions of adolescents towards the disapproval shown by health workers, further limit access to services, even though these services exist. In addition, there are also legal barriers related to the provision of services and information to youth groups. Many of the adolescents lack or do not have a stable relationship with their parents or other adults, with whom they should be able to talk about reproductive health issues.